Long‐term monitoring of a mercury contaminated estuary (Ria de Aveiro, Portugal): the effect of weather events and management in mercury transport. Issue 2 (5th November 2012) - Coelho, J. P.; Pato, P.; Henriques, B.; Picado, A.; Lillebø, A. I.; Dias, J. M.; Duarte, A. C.; Pereira, M. E.; Pardal, M. A.
ABSTRACT The main aim of this research was to assess the mercury transport from an estuarine basin with a background of anthropogenic contamination during a spring tidal cycle (year 2009) and compare it with two previous tidal cycles (years 1994 and 1999), as part of a long‐term monitoring program. Results showed that effective mercury transport occurs both in the dissolved and particulate fractions (0.18 and 0.20 kg per tidal cycle, respectively), and despite an overall decrease in environmental contamination, results more than double previous findings on particulate transport in the system. These findings result essentially from changes in the tidal prism (net export of 2 million m3 of water), given that both dissolved and particulate concentrations did not increase over time. Hydrodynamic simulations were performed to evaluate the effect of physical disturbance (dredging) and weather events (increased freshwater flow) in these processes, and results suggest the increased freshwater flow into the system as the main forcing function for the mercury transport increment. These results highlight the importance of long‐term monitoring programs, since despite an overall improvement in local contamination levels, the enhancement of transport processes through hydrological changes increases environmental pressure away from the contamination source. Copyright © 2012 John Wiley & Sons, Ltd.